Art Music by Caribbean Composers: Antigua and Barbuda - Gangelhoff, Christine; LeGrand, Cathleen (International Journal of Bahamian Studies, 2013)
The steel pan was introduced from Trinidad in 1945 and quickly gained popularity (De Jong, 2005). The first steel band in the Caribbean, the Hell’s Gate Steel Orchestra, was formed in the late 1940’s and is still a force in the Antiguan steel pan scene (De Jong, 2005). More steel bands quickly arose and “the steel pan became the center of cultural life on Antigua and Barbuda” (De Jong, 2005, para. 3).